Two new diketopiperazines and a new glucosyl sesterterpene from Alternaria alternata, an endophytic fungi from Ceratostigma griffithii. (December 2015) - Guo, Da-Le; Zhao, Min; Xiao, Shi-Ji; Xia, Bing; Wan, Bo; Gu, Yu-Cheng; Ding, Li-Sheng; Zhou, Yan
Graphical abstract: Highlights: Two new diketopiperazine derivatives (1 -2 ) were isolated from Alternaria alternata . A new glucosyl sesterterpene (3 ) was isolated from Alternaria alternata . All the compounds were assayed for antimicrobial activity. Abstract: Two diketopiperazine derivatives, altenarizines A (1 ) and B (2 ), and a new glucosyl sesterterpene, 24-α-d -glucosyl-(−)-terpestacin (3 ), together with two known phytotoxic sesterterpenes, (−)-terpestacin (4 ) and fusaproliferin (5 ), were isolated from the fermentation broth of an endophytic fungus Alternaria alternata, which was obtained from the fresh root of Ceratostigma griffithii . Structures of all the isolates were identified by spectroscopic data.